Education for Children with Disabilities – Issues in Access, Challenges, Solutions - Bhandary, Ashok (Kalika Journal of Multidisciplinary Research, 2024)
Education is undoubtedly important for the development of all children, but it becomes a matter of even greater significance for children who are disabled. For children with disabilities, their prospects in life for equitable social and economic opportunities are disproportionately jeopardized when they lack access to quality education. The aim of this research is to understand the issues in education faced by children with disabilities, specifically, the challenges they face. Based on perspectives of disability education and inclusive education, this research utilizes a descriptive study design to understand the issues in education for children with disabilities. In Nepal, a signatory state of the United Nations Convention on the Rights of the Child, significant challenges persist in access to quality education for children with disabilities. Preliminary interviews from six students and their teachers revealed systemic problems in access and delivery of education for children with disabilities. Guided by these prompts and insights, a comprehensive survey instrument was prepared for data collection with students. Field based survey data was collected with 66 students. Additionally, seven interviews were conducted with teachers, administrators, and administrators who worked with these students. The survey data was analysed using IBM’s SPSS Version 23. Insights from data analysis and interviews revealed that children with disabilities face a critical shortage of qualified teachers, learning resources and disabled-friendly physical infrastructure. The primary implication of this study is towards Nepal Government’s education policymakers. The ultimate objective of this study was to shed light on issues of disability education and thereby increase access and quality of education for children with disabilities in Nepal[1].